Analisis Hukum Adat Dayak Kalis di Kalimantan Barat - Muzakki Ayatulloh GH; Ronan Marsa Salatun; Arief Fuad Dimyati; Rahayu Sri Utami (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the customary law system that applies in the Dayak Kalis community in West Kalimantan and examine its relationship with national formal law. Dayak Kalis customary law is an unwritten legal system that develops from the norms and customs of indigenous communities, and functions as a guideline in resolving disputes and regulating social life. In practice, this law emphasizes the values ​​of restorative justice and deliberation by consensus, with types of punishments adjusted to the level of violation, such as Saut, Setanga'Baar, Pati Nyawa, and Adat Kampung. The study uses a normative method with a document approach, legislation, and legal theory. The results of the study indicate that Dayak Kalis customary law remains recognized in the national legal system as long as it does not conflict with generally applicable laws. The existence of this customary law reflects the importance of preserving local wisdom as an integral part of the pluralistic Indonesian legal system.